Deep Venous Thrombosis in Patients with Erythema Nodosum Leprosum in the Use of Thalidomide and Systemic Corticosteroid in Reference Service in Belo Horizonte, Minas Gerais - Luiz Alberto Bomjardim Pôrto; Maria Aparecida de Faria Grossi; Edilamar Silva de Alecrim; Marcus Henrique de Souza Brito Xavier; Frederico Paiva e Silva; Amalia Sathler Pires; Fabianny Sanglard da Silva; Sandra Lyon (Case Reports in Dermatological Medicine)
Introduction. Erythema nodosum leprosum (ENL) is a type of lepra reaction treated with corticosteroids and thalidomide, but this association increases the risk of deep venous thrombosis (DVT). Objective. To report cases of ENL with DVT in the use of thalidomide/corticosteroid associated. Methodology. The study was conducted between December 2015 and December 2016 at the Eduardo de Menezes Hospital (HEM-FHEMIG). Results. A clinical case series of 16 patients, eight from HEM-FHEMIG and eight from the literature. DVT occurred on 4 continents, mainly in adults and men. All patients were multibacillary; four people had pulmonary embolism (PE); there were 11 unilateral and five bilateral DVT cases; 12 cases were proximal, two distal, and two unspecified. Pharmacological thromboprophylaxis was used on two individuals. Outcome after DVT, 14 patients improved, one had sequelae, and one died. Discussion. DVT increased in association with thalidomide/corticosteroid in multiple myeloma, but this complication is poorly described in ENL. In proximal DVT, there was a greater risk of PE and sequelae venous insufficiency. After DVT, start anticoagulation. ASA 100mg/day as prophylaxis for DVT in case of this drug association in ENL is recommended. Conclusion. The article illustrates the incidence increase of DVT because of the thalidomide/corticosteroid combination in ENL. When this association is necessary, use ASA 100mg/day as prophylaxis.